2021
DOI: 10.1155/2021/3221448
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fractal Analysis in Detecting Trabecular Bone Changes in Periapical Radiograph of Patients with Periodontitis

Abstract: Introduction. Evaluation of detailed features of the supporting bone is an important step in diagnosis and treatment planning for teeth with clinical attachment loss. Fractal analysis can be used as a method for evaluating the complexity of trabecular bone structures. The aim of this study was to evaluate the trabecular bone changes in periapical radiographs of patients with different stages of periodontitis using fractal analysis. Methods. This comparative cross-sectional study was performed on patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…In the present study, this information was absent in the records because radiology clinics do not routinely collect these data. However, previous studies using FA to investigate dental and bone alterations have found consistent results for the method (Pârvu et al, 2014;Soltani et al, 2021;Tözüm et al, 2016;Uğur Aydın et al, 2019;Yu et al, 2009). Moreover, a systematic review of publications on FA reported similar findings for range of FD values using the boxcounting method to those of the present study (Kato et al, 2019).…”
Section: Discussionmentioning
confidence: 66%
“…In the present study, this information was absent in the records because radiology clinics do not routinely collect these data. However, previous studies using FA to investigate dental and bone alterations have found consistent results for the method (Pârvu et al, 2014;Soltani et al, 2021;Tözüm et al, 2016;Uğur Aydın et al, 2019;Yu et al, 2009). Moreover, a systematic review of publications on FA reported similar findings for range of FD values using the boxcounting method to those of the present study (Kato et al, 2019).…”
Section: Discussionmentioning
confidence: 66%
“…This is with agreement with another study which reported; that nonsurgical periodontal therapy did not produce any radiographic changes in the bone level for sites with horizontal bone loss (29) . Phenytoin group showed, no difference between baseline and 1month while the statistically significant differences were exhibited after 3 and 6 months when compared 29 baseline that can be justified by the new alveolar bone began filling trabecular bone after 64 days (30) .…”
Section: Discussionmentioning
confidence: 79%
“…The assessment aimed to provide insights into the composition and diversity of oral microbiota in the context of early plaque formation. Kao et al [ 21 ] conducted an observational trial involving 29 patients who were administered anti-cancer medication for squamous cell carcinoma. GS was utilized to assess specific variables related to the impact of cancer treatment on oral microbiota, contributing to our understanding of the oral microbiome in cancer patients.…”
Section: Resultsmentioning
confidence: 99%